Adaption strategy of fisherman to climate change: A case study from Limau Sub-District, Tanggamus Regency. Issue 1 (1st May 2022) - Mutolib, A; Rahmat, A; Listiana, I; Yanfika, H; Widyastuti, R A D; Riantini, M
Abstract: Climate change is a natural phenomenon that occurs all over the world and has a negative impact on many sectors, one of which is the fishery sector. One of the communities that are most vulnerable to the impact of climate change is the fishing community in coastal areas. Fishermen depend on the availability of fish in the sea, as well as the weather and other aspects related to climate and nature. This study aims to identify the fishermen's efforts and adaptation strategies towards climate change. Data collection was carried out from July to August 2020 in Limau Sub-District, Tanggamus Regency with a total respondent number of 80 fishermen households. Respondents were determined through the approach of simple random sampling. The data collected consisted of both qualitative and quantitative data. Data collection was performed through the method of survey, Focus Group Discussion (FGD), and interviews with key informants. Data collected was analyzed using the Qualitative Descriptive approach. The results of the study show that fishermen in Limau Sub-district have made some adaptations to climate change in coastal areas through income diversification, diversification of fishing gear, migration, and social network development among fishermen